IDENTIFIKASI HYPOXIA DI TELUK HURUN LAMPUNG - Santoso, Arif Dwi (Jurnal Teknologi Lingkungan, 2005)
This study was carried out to describe the characteristics of hypoxia in the tropical coastal sea. The general oceanographic surveys were conducted two times in Hurun Bay, 5-7 February and 17-19 February, 2003. And also, a day-night survey (25 hours survey) and the continuous monitoring of water temperature, current and meteorology were carried out. The monitoringdata of water temperature indicated that the seasonal variation and the spatial in temperature in Hurun Bay were small. The difference in temperature between the surface and bottom water was less than 1.3 oC. The water temperature increased from February and the highest in April.It gradually decreased to late June and a sudden decrease occurred in the early July. The lowest temperature was observed in September and then it increased again. The seasonal variation in the thermal stratification was not happened. Instead of the weak thermal stratification, a sharp picnocline was formed around 20m in the dry season. The water below the picnoline was colder and more saline and contained less DO than the overlaying water. The cold water mass which has high salinity and lower DO was situated along bottom deeper than 20m on 17-19 July. The lowest DO in this water mass was 0.4 mg/l. Such a cold water mass appeared in early July and it propagated from offshore to the coast. The oxygen consumption rate of the water column was about 0.1 mgO2/L/hour in Hurun Bay. Comparing these oxygen consumption rates and the DO of water, if the oxygen supply was restricted, the water in Hurun Bay could become hypoxic easily.